1:1 complex of 4-nitrobenzoic acid and 4-nitropyridine N-oxide - Moreno-Fuquen, R.; de Castro, EVR; Moreno, M.; Santos, RHD; Montano, A. M. (Munksgaard Int Publ Ltd, 2000)
In the title co-crystal, C7H5NO4. C5H4N2O3, the two components are linked by an intermolecular hydrogen band between the O-H and N-O groups [O ... O 2.577(3) Angstrom]. The interplanar angle between the planes of the rings of the molecules is 5.3 (2)degrees. The rings are stacked in the crystal with a mean interplanar distance of 3.279 (3) Angstrom.